Analiza czynników sprzyjających powodziom = Flooding factors analysis - Asani, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In many countries, now and again step out smaller or larger floods. They send large damages and require some gigantic expenses on their liquidation. The pronouncements waters from his bed hapend while large falls, spring melting snows and also stormy arrangements (on sea coastal areas). The building of flood protections is very expensive. However, realized investments not always keep carry out their plow. It can be caused from many factors like e.g. their inappropriate location or bad technical state.
Keywords: ochrona przeciwpowodziowa; czynniki sprzyjające powodziom; flood protection; flooding factors